(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Dengue fever, borne by Aedes aegypti mosquito, is one of the most common and most prevalent forms of flavivirus infections in humans, endemic in tropics and warm temperate regions of the world. We report a spectrum of ocular manifestations of dengue fever along with its associated laboratory findings. To study the ocular manifestations associated with dengue fever. This study was conducted in 600 patients hospitalized with diagnosis of dengue fever over a period of 3 months from March 2019 to May 2019. All patients underwent complete evaluation with respect to systemic and ophthalmic examination in different institutions of Bangladesh. A total of 600 patients were diagnosed with dengue fever; of which, 375 (62.5%) were men and 225 (37.5%) were women. Mean age was 32 years (20–60 years). Only 195 patients (32.7%) had complaints of retrobulbar pain in the eyes. 10 patients (1.67%) had blurring of vision. Ocular findings were present in 340 patients (56.7%). Most common anterior segment findings were subconjunctival haemorrhage in 275 patients (45.8%). Posterior segment findings were present in 80 patients (13.3%); of which, 70 (87.5%) had retinal haemorrhages. Ocular changes had resolved in all the cases, which came for follow-up in 8–10 weeks. It was mostly attributed to the improving platelet count. The incidence of ocular complications in dengue fever is increasing, hence all patients with dengue should be referred to an ophthalmologist to prevent any sight-threatening BSMMU J 2022; 15(1): 16-19